METODE LIKUIDASI BANK PADA BANK PERKREDITAN RAKYAT - Ashari, Hasan; Nugrahanti, Trinandari Prasetyo (Program Studi Akuntansi FPEB UPI, 2018)
This study aims to explain the application of liquidation and accounting methods based on liquidation by LPS in the implementation of liquidation compared with current standards. The methodology in this research is qualitative and the nature of this research is descriptive analysis. Based on the results of this study it is concluded that in the implementation of liquidation there are critical issues that require the attention of LPS such as the fraud rate that occurred before the bank was liquidated, flow of documentation and information of failed bank, personnel readiness, supervision, handling of liquidation assets and limitations of liquidation guidelines. The critical issues encountered above will ultimately affect the recovery rate and the remaining liquidation assets. In relation to the implementation of liquidation-based accounting standards in liquidation implementation, LPS has implemented liquidation-based accounting that partially meets ASU 2013-07, which is related to the measurement of assets and liabilities. However, there are still limitations regarding the reporting of net assets and changes in net assets in the liquidation process periodically